Korelasi Penerbitan Kartu Kredit Syariah dengan Perubahan Perilaku Konsumsi Umat Islam - Miftakhul Huda (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Sharia cards are sharia banking products that include new ones, in practice need to get special attention to be in accordance with the concept of sharia. Sharia card issuance is very beneficial for humans, which makes it easier for people to make payments, and gives a sense of security to humans because they do not need to carry a lot of money. Supposedly, the benefits obtained are not only worldly benefits, but there must be benefits from the afterlife. Islamic banks look at financing products as one of the services offered. There is a very important limitation that must be realized by Islamic banks, namely the provisions in sharia principles regarding credit cards and their influence on the consumptive behaviour of the community, especially the Muslim community. Because it is not possible, there are credit cards that can be presented for the freedom to transact into cards for convenience and concepts that exist in the concept of Islamic economics.